The Persisting Problem of Persistence: A Call for an Alternative Theory - Badejo, Omobola Olufunto (Conatus - Journal of Philosophy, 2022)
The question of how to characterise the diachronic identity of a concrete particular within a metaphysical framework is the problem of persistence. There are two major theories, Endurantism and Perdurantism affirming a problem of persistence for concrete particulars. While Endurantism, on the one hand, argues that concrete particulars persist wholly, Perdurantism, on the other hand, argues that they persist as temporal slices. This paper argues that neither Endurantism nor Perdurantism adequately characterise the persistence of concrete particulars. This is because there is an impasse between these two major theories of persistence. The article concludes that hence, there is a need for another hypothesis or theory of persistence to address the problem of persistence in metaphysics. This paper broadens the discourse on persistence of concrete objects beyond a debate between Endurantism and Perdurantism. The paper uses the methods of conceptual analysis and philosophical argumentation.